“4Sens Pro” food’s biosensor / Muhamad Hazman Fitri Mohd Nazri ... [et al.] - Mohd Nazri, Muhamad Hazman Fitri; Seri Vejay, Muhammad Alif Haikal; Sofian, Ahmad Nazhim; Muzaffar, Muhammad Aqif (2024)
Biosensors can be designed to detect the presence of specific microorganisms associated with spoilage, such as bacteria, yeasts, and molds. These sensors not only identify these spoilage-causing organisms but can also detect changes in the levels of gases like ammonia and carbon dioxide, which are often by products of microbial activity and early indicators of food deterioration. By providing early warnings, biosensors help in maintaining food quality and safety. In addition to biosensors, IoT sensors play a crucial role in monitoring a variety of environmental conditions in real-time, including temperature, humidity, air quality, and more. These sensors continuously track the conditions that affect product quality, ensuring that optimal storage and handling conditions are maintained. By integrating biosensors with IoT sensors, a comprehensive system is created that not only detects spoilage but also prevents it by monitoring and controlling the factors that contribute to it.